Hypopituitarism following cerebral oedema with diabetic ketoacidosis. Issue 4 (1st October 2002) - Dunlop, K A; Woodman, D; Carson, D J
Abstract : Clinical evidence of cerebral oedema occurs in approximately 1% of diabetic ketoacidosis episodes. Mortality from this serious complication is falling, but little is known of long term outcome. We describe hypopituitarism and executive dysfunction developing two years after cerebral oedema complicating diabetic ketoacidosis in a 12 year old with type 1 diabetes.